A cysteine protease inhibitor of Plasmodium berghei Is essential for exo-erythrocytic development - Lehmann, Christine; Heitmann, Anna; Mishra, Satish; Burda, Paul-Christian; Singer, Mirko; Prado, Monica; Niklaus, Livia; Lacroix, Céline; Ménard, Robert; Frischknecht, Friedrich; Stanway, Rebecca; Sinnis, Photini; et al. (PLoS pathogens, 2014)
Plasmodium parasites express a potent inhibitor of cysteine proteases (ICP) throughout their life cycle. To analyze the role of ICP in different life cycle stages, we generated a stage-specific knockout of the Plasmodium berghei ICP (PbICP). Excision of the pbicb gene occurred in infective sporozoites and resulted in impaired sporozoite invasion of hepatocytes, despite residual PbICP protein being detectable in sporozoites. The vast majority of these parasites invading a cultured hepatocyte cell line did not develop to mature liver stages, but the few that successfully developed hepatic merozoites were able to initiate a blood stage infection in mice. These blood stage parasites, now completely lacking PbICP, exhibited an attenuated phenotype but were able to infect mosquitoes and develop to the oocyst stage. However, PbICP-negative sporozoites liberated from oocysts exhibited defective motility and invaded mosquito salivary glands in low numbers. They were also unable to invade hepatocytes, confirming that control of cysteine protease activity is of critical importance for sporozoites. Importantly, transfection of PbICP-knockout parasites with a pbicp-gfp construct fully reversed these defects. Taken together, in P. berghei this inhibitor of the ICP family is essential for sporozoite motility but also appears to play a role during parasite development in hepatocytes and erythrocytes.
Gesehen am 31.08.2020